2014
DOI: 10.1158/0008-5472.can-13-1747
|View full text |Cite
|
Sign up to set email alerts
|

Activated ERBB2/HER2 Licenses Sensitivity to Apoptosis upon Endoplasmic Reticulum Stress through a PERK-Dependent Pathway

Abstract: HER2/Neu/ERBB2 is a receptor tyrosine kinase overexpressed in approximately 20% of human breast tumors. Truncated or mutant isoforms which show increased oncogenicity compared to the wild-type receptor are found in many breast tumors. Here we report that constitutively active ERBB2 sensitizes human breast epithelial cells to agents that induce endoplasmic reticulum (ER) stress, altering the unfolded protein response (UPR) of these cells. Deregulation of the ERK, AKT and mTOR activities elicited by mutant ERBB2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 52 publications
7
75
0
Order By: Relevance
“…Importantly, the authors seem focused to disprove one study, while ignoring numerous studies that have shown a role of DR5 and caspase-8 in apoptosis activated by different UPR-inducing stimuli such as thapsigargin or glucose deprivation 3,8,9 , Altogether, these data indicate that DR5, caspase-8, Bim, Bid and Noxa are required for ER stress and UPR-mediated death in a cell type-dependent manner. …”
Section: Correspondencementioning
confidence: 96%
“…Importantly, the authors seem focused to disprove one study, while ignoring numerous studies that have shown a role of DR5 and caspase-8 in apoptosis activated by different UPR-inducing stimuli such as thapsigargin or glucose deprivation 3,8,9 , Altogether, these data indicate that DR5, caspase-8, Bim, Bid and Noxa are required for ER stress and UPR-mediated death in a cell type-dependent manner. …”
Section: Correspondencementioning
confidence: 96%
“…(HER2/Neu) sensitizes human breast epithelial cells to thapsigargin treatment resulting on cell death due to an altered unfolded protein response [60]. Mutant ERBB2 triggers a deregulation of ERK, AKT and the mTOR pathway which results in UPR-dependent apoptosis in those cell lines.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Human ESCC cell lines EC1, EC109, Kyse450, Kyse30, and Kyse510 were routinely cultured in Dulbecco's Modified Eagle's Medium (Hyclone), containing 10% FBS (Biochrom, AG) and 1% penicillin-streptomycin solution, at 37 C with 5% CO 2 . MLN4924 was synthesized and prepared as previously described (3,25,26).…”
Section: Cell Lines Culture and Reagentsmentioning
confidence: 99%
“…Previous studies demonstrated that activating transcription factor 4 (ATF4) serves as a substrate of CRL/SCF bTrcp ubiquitin ligase (21,34,35), and transcription factor CHOP, a classical downstream target of ATF4, can regulate the transactivation of DR5 (36)(37)(38). Based on this, we hypothesized that MLN4924 may induce ATF4 accumulation due to the inactivation of CRL/ SCF bTrcp ubiquitin ligase which requires nedd8 conjugation to its essential subunit cullins for activation, and therefore transactivates CHOP and DR5 to activate extrinsic apoptosis.…”
Section: Dr5 Is Transactivated By Activating Transcription Factor 4/cmentioning
confidence: 99%